2015
DOI: 10.3892/mco.2015.590
|View full text |Cite
|
Sign up to set email alerts
|

A Surveillance, Epidemiology and End Results-Medicare data analysis of elderly patients with glioblastoma multiforme: Treatment patterns, outcomes and cost

Abstract: Abstract. The Surveillance, Epidemiology and End Results (SEER) database was used to determine the treatment patterns, outcomes and cost of therapy in elderly patients with glioblastoma multiforme (GBM). The SEER-Medicare linked database was used to identify patients aged >66 years with GBM diagnosed between 1997 and 2009. The patients were stratified by initial treatment following diagnostic surgery (resection or biopsy) into 6 groups as follows: No treatment, standard radiation therapy (SRT) with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
4
25
1
Order By: Relevance
“…Those results are similar to findings reported in other retrospective analyses of elderly gbm patients [15][16][17][18] . Among elderly patients who received radiotherapy, os was found to be prolonged in those who had received combined-modality treatment: median survival was 11.3 months in patients who received chemoradiation compared with 4.6 months in those treated with radiation only.…”
Section: Figuresupporting
confidence: 82%
See 2 more Smart Citations
“…Those results are similar to findings reported in other retrospective analyses of elderly gbm patients [15][16][17][18] . Among elderly patients who received radiotherapy, os was found to be prolonged in those who had received combined-modality treatment: median survival was 11.3 months in patients who received chemoradiation compared with 4.6 months in those treated with radiation only.…”
Section: Figuresupporting
confidence: 82%
“…In a retrospective analysis of American patients more than 65 years of age with a new diagnosis of gbm between 1997 and 2009, median survival ranged between 2 months (for patients who received no postoperative therapy) and 11 months (for those who received standard combined chemoradiation). In addition, increasing age beyond 65 years was associated with shorter survival, with patients 65-75 years of age surviving a median of 8 months after diagnosis, compared with 4 months for patients 75 years of age and older 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,22 In addition to age, patient demographic and treatment factors, including sex, race, and treatment facility type, predict the receipt of adjuvant therapy. The youngest patients in our study were significantly more likely to receive adjuvant therapy with CRT, CT, or RT than no adjuvant therapy compared with the oldest patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies in the literature have revealed that age is the most common and important prognostic variable for GBM. 20,21 Notably, according to our results, age alone is an important factor in the decision-making for treatment selection. Nevertheless, the most suitable treatment option should not be selected on the basis of the age factor alone, it should, in fact, consider the patient's overall health status, desires, and expectations.…”
Section: Discussionmentioning
confidence: 99%